Electrophoretic deposition of novel semi-permeable coatings on 3D-printed Ti-Nb alloy meshes for guided alveolar bone regeneration. Issue 2 (February 2022) - Zhao, Danlei; Dong, Haoran; Niu, Yuting; Fan, Wenjie; Jiang, Muqi; Li, Ke; Wei, Qingsong; Palin, William M.; Zhang, Zhen
Highlights: Ti-Nb alloy meshes with various lattice were fabricated by selective laser melting. Novel semi-permeable coatings were developed on 3D-printed Ti-Nb alloy meshes for GBR. Antibacterial activity and biocompatibility were achieved in the CSGDox coating. CSGDox coating was capable to inhibit fibroblast infiltration and allow protein transport. Abstract: Objective: Guided bone regeneration (GBR) techniques use barrier membranes to augment the alveolar ridge for the site-specific growth of bone defects. However, current approaches using cast metal substructures exhibit poor adaptation to the surgical site and increased risk of infection. This study aimed to fabricate multi-functional coatings with 3D-printed porous titanium-niobium (Ti-Nb) alloy meshes to maintain space, prevent the ingrowth of fibroblasts and inhibit the colonization of bacteria for GBR. Methods: Ti-Nb alloy meshes were prepared by selective laser melting (SLM) and used as substrates for novel surface coatings. Porous chitosan (CS)/ gelatin (G)/ doxycycline (Dox) coatings were formed on the meshes using electrophoretic deposition (EPD) and freeze-drying. The process of EPD was characterized through Fourier transform infrared spectroscopy (FT-IR), zeta potential, and particle size analysis. The cytotoxicity of the coatings was evaluated through the culture of osteoblasts and immunostaining. The antibacterial activity of the coatings was tested using inhibition zone tests against Staphylococcus aureus ( S. aureus ) and scanning electron microscope (SEM). The inhibition of fibroblasts infiltration and nutrients transfer properties were analyzed using immunostaining and permeability tests. Results: High yield strength (567.5 ± 3.5 MPa) and low elastic modulus (65.5 ± 0.2 GPa) were achieved in Ti-Nb alloy bulk samples. The data of zeta potential, FT-IR and SEM indicated that porous spongy coatings were chemically bonded following EPD. In vitro analysis of CSGDox1 (containing Dox at 1 mg·mL −1 ) coating revealed its antibacterial effect and biocompatibility. Moreover, the CSGDox1 coating was proved to be effective for preventing the ingrowth of fibroblasts, whilst allowing the infiltration of nutrients. Significance: This study verified that the EPD of CSGDox coatings on the 3D-printed Ti-Nb meshes can maintain space, provide antibiotic release whilst maintaining a barrier against soft-tissue growth, which is essential for the success of GBR treatment.